Strategy of incorporating Ni-based braze alloy in cold sprayed Inconel 718 coating - Sun, Wen (2021)
Ni-based superalloy (Inconel 718) and Ni-based braze alloy (MAR-M 002) composite coatings were deposited on Inconel 718 substrates via a high-pressure cold spray process. The effects of post heat treatment on microstructural evolution and chemical diffusion of the composite coatings were systematically investigated. The microstructures of the powders and composite coatings were investigated using scanning electron microscopy, electron backscatter diffraction, energy-dispersive X-ray spectroscopy and nanoindentation. After cold spray deposition, it was found that MAR-M 002 particles were uniformly distributed within the as-sprayed composite coatings. During the heat treatment process, it was noted that the diffusion of chemical species occurred across the Inconel 718 and MAR-M 002 particulate interfaces with the width of the diffusion zone being around 10 μm. The enhanced chemical diffusion between Inconel 718 and MAR-M 002 particles could effectively heal out the splat boundaries and reduce coating porosity, which was proved with the microstructure analysis. The effect of chemical diffusion on interparticle bonding strength was investigated through tensile testing. The heat-treated Inconel 718/MAR-M 002 composite coating had a tensile strength of about 810 MPa that was about 17% higher compared to the heat-treated pure Inconel 718 coating. From the SEM observations, the fractured surface of the heat-treated IN718/MAR-M 002 composite specimen was characterized by the presence of more dimples, which indicated a higher fraction of metallurgically bonded interparticle boundaries. These results demonstrated that the proposed methodology for the formation of Inconel 718/MAR-M 002 composite deposits was beneficial for improving the interparticle bonding strength in the deposits.